Body condition scores and biochemical changes across gestation trimesters in Dorper ewes under free-grazing conditions (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
The body condition score (BCS) and blood biochemical parameters are key indicators of the physiological and nutritional challenges for pregnant ewes. This study aims to evaluate the trimester-specific changes in BCS and blood biochemical parameters in Dorper ewes reared under a free grazing system. Twenty pregnant Dorper ewes were selected for this study, BCS and blood samples were collected during the first, second, and third trimesters. The BCS were assessed on a five-point scale, and the serum's hematological profiles and pregnancy-related biochemical parameters were analysed. Repeated measures of ANOVA were used to analyse the significant trimester-specific variations. Results show the BCS shifted as gestation progressed, with most ewes in BCS 3, whereas a decline in BCS 4 and 5 indicates increasing energy demands and the use of body reserves in the later trimester. The haematological profile has no significant deviations and is within physiological ranges across trimesters. The changes in biochemical parameters throughout the gestation period showed that blood urea nitrogen (BUN), albumin (ALB), and alanine aminotransferase (ALT) peaked in the third trimester, while the cholesterol (CHOL) significantly surged (P
Keywords: Serum biochemical parameters; pregnancy; Dorper; ewes; free-grazing system